Nonpharmacologic treatment for elderly with constipation: a systematic review and meta-analysis - Xu, Lingyu; Leng, Yan; Dai, Peng; Gao, Huize; Chu, Yunhang; Chen, Xingyu; Yang, Ming; Li, Xia; Yang, Tiezheng (Frontiers in Medicine, 2025)
ObjectiveThis study evaluated the efficacy and safety of non-pharmacological interventions such as acupuncture, abdominal massage, ear acupoints, probiotics, and dietary fiber in the treatment of constipation in the elderly.MethodsRandomized controlled trials (RCTs) published up to March 2025 were retrieved from Cochrane Library, PubMed, Web of Science, Embase, and Chinese databases. The research quality was evaluated using the Cochrane risk of bias assessment tool. Data analysis was performed using RevMan5.4.1 and Stata software. Grade evidence quality was assessed on the analysis’s outcome indicators.ResultsForty-one studies involving 3,005 patients aged ≥60 years were included. The non-pharmacologic treatment group demonstrated significantly higher efficacy compared to the control group (RR = 1.15, 95% CI = 1.09 to 1.21, p < 0.00001), with high heterogeneity (I2 = 58%, p < 0.0001). Subgroup analysis revealed superior therapeutic efficacy of acupuncture (n = 15), abdominal massage (n = 11), and ear acupoint therapy (n = 3) compared to the control group. The incidence of adverse events in the non-drug-treated group was lower than that in the control group (RR = 0.35, 95% CI = 0.16 to 0.74, p = 0.006); its heterogeneity was (I2 = 46%, p = 0.04). Meta-analysis of the Constipation-Related Quality of Life Scale (CQLS) revealed that the non-pharmacological treatment group had a more significant therapeutic effect on anxiety or distress. In addition, in the Bristol stool scale, the non-pharmacologic treatment group had better results (standardized mean difference (SMD) = 0.87, 95% CI = 0.14–1.60, p = 0.02), and better improvement was achieved after the treatment cycle >4 weeks. In the CSBM scale, the non-pharmacological treatment group showed better efficacy (SMD = 0.44, 95% CI = –0.52–0.12, p = 0.03). Symptom score analysis showed that in addition to abdominal distension, eight indicators, including abdominal pain, number of bowel movements, and stool consistency, in the non-pharmacologic treatment group were significantly improved (p < 0.05). Some RCTs included in this study had publication bias, and the sensitivity analysis results were robust.ConclusionNon-pharmaceutical interventions are better than conventional treatments in the treatment of constipation in the elderly, and long-term intervention has more significant effects. However, due to different intervention regimens, inconsistent treatment time, and methodological defects included in the study, there is a high degree of heterogeneity (CQLS, Bristol, and I2 of symptom scores often > 90%). In the future, large-sample, high-quality RCTs are needed to verify their long-term efficacy and related mechanisms.